Adopsi Teknologi dan Analisis Finansial pada Pengolahan Minuman Ringan dan Sirup Air Kelapa di Kabupaten Minahasa - DANIEL J. TORAR (Buletin Palma, 2010)
Adoption of Technology and Financial Analysis from in the Processingof Soft Drink and Syrup Derived Coconut Water in Minahasa RegencyThe research was conducted in the Village Ranowangko and village Sarani Matani Tombariri District, and Village Pineleng Two and village Kali District Pineleng Minahasa District of North Sulawesi Province in September - October 2008. The method used in this research was descriptive and normative survey directly applied to the farmer. Determination of sampled farmers by random sampling, and each village was taken 30 farmers. Results showed that financial analysis and processing of soft drink syrup coconut water was feasible, as indicated by the higher value of BCR. Adoption level by the farmers to the processing technology of soft drinks and syrups coconut water is low (0 - 59.99%) for 34 farmers (28.33%), moderate (60 to 79.99%) for 71 farmers (59.16% ), and high (80-100%) for 15 farmers (12.50%).